2014
DOI: 10.1007/s00795-014-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

The elongation of primary cilia via the acetylation of α-tubulin by the treatment with lithium chloride in human fibroblast KD cells

Abstract: Primary cilium, an organelle found on nearly every cell in the human body, typically serves as the mechanical sensor of the cell. Lithium ion is known to promote the elongation of primary cilia in a variety of cell types, but it is unknown whether lithium is involved in the acetylation of α-tubulin which is essential for the assembly of primary cilia. In order to reveal the relationship between the elongation of primary cilia with lithium and the acetylation of α-tubulin, we first observed the formation and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 50 publications
0
37
1
Order By: Relevance
“…Nakakura et al (14) reported that in fibroblasts, LiCl‐mediated inhibition of GSK releases an inhibitory block on the enzyme α‐tubulin acetyl transferase 1, causing a dramatic increase in whole‐cell acetylated tubulin levels and an increase in cilia length. Immunocytochemistry revealed that the distribution of acetylated tubulin was altered in chondrocytes treated with 50 mM LiCl ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakakura et al (14) reported that in fibroblasts, LiCl‐mediated inhibition of GSK releases an inhibitory block on the enzyme α‐tubulin acetyl transferase 1, causing a dramatic increase in whole‐cell acetylated tubulin levels and an increase in cilia length. Immunocytochemistry revealed that the distribution of acetylated tubulin was altered in chondrocytes treated with 50 mM LiCl ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Cilia assembly and disassembly is initiated at the distal tip; IFT is thus essential to maintain the size of the ciliary compartment (29). Studies have shown that LiCl promotes significant elongation of the ciliary axoneme in fibroblasts (14, 15) and neuronal cells (13); however, the consequences of this elongation for cilia‐mediated signaling pathways has not been explored.…”
mentioning
confidence: 99%
“…Treatment of human KD diploid fibroblasts with 25-50 mM LiCl promotes a-tubulin acetylation and elongation of primary cilia [137]. siRNA-mediated depletion of ATAT1 expression showed that this enzyme is required for induced a-tubulin acetylation in these cells [137].…”
Section: Tubulin Acetylation and Ciliamentioning
confidence: 99%
“…Treatment of human KD diploid fibroblasts with 25-50 mM LiCl promotes a-tubulin acetylation and elongation of primary cilia [137]. siRNA-mediated depletion of ATAT1 expression showed that this enzyme is required for induced a-tubulin acetylation in these cells [137]. Similar depletion of ATAT1 expression in human telomerase-expressing retinal pigment epithelial cells slows down the kinetics of ciliary disassembly [48].…”
Section: Tubulin Acetylation and Ciliamentioning
confidence: 99%
“…Immunofluorescence methods were performed as described previously [13, 15]. Briefly, LβT2 cells and AtT20 cells were transfected with pCMV-Gluc 2 or pcDNA3.1 as described above and cultured on poly-D-lysine-coated cover glass.…”
Section: Methodsmentioning
confidence: 99%